Algebra 2 (1st Edition)

Published by McDougal Littell
ISBN 10: 0618595414
ISBN 13: 978-0-61859-541-9

Chapter 13, Trigonometric Ratios and Functions - 13.1 Use Trigonometry with Right Triangles - 13.1 Exercises - Mixed Review - Page 858: 49


$x=0; y=-3$

Work Step by Step

Since we are given two equations $4x-6y=18$ and $-2x+y=-3$ Now, multiply the equation $-2x+y=-3$ by $2$; thus we have $4x-6y=18$ and $-4x+2y=-6$ After solving, we get $-4y =12 \implies y= -3$ Then, $-4x+2(-3)=-6$ This implies $4x=0 \implies x=0$ Hence, $x=0; y=-3$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.